A study on strategy development for e-commerce businesses with clustering and spherical fuzzy analytic hierarchy process - Tepe, Serap; Eti, Serkan (Niğde Ömer Halisdemir University, 2022)
E-Commerce is a shopping method that allows trading or placing an order for any product or service on a website with various payment methods. This method is gaining importance day by day and increasing its market share. Although the reasons for choosing e-commerce for consumers are different from each other, in general, criteria such as time, payment options and individualization affect preferences. In this study; e-commerce sites were compared, and 14 e-commerce sites were determined as alternatives based on expert opinions. These identified e-commerce sites were evaluated in terms of criteria such as brand image & reliability, campaign, cargo speed, packaging, payment options, personnel, call center services and functionality of the application. In the first part of the study, two clusters of e-commerce sites were created using cluster analysis. These clusters are grouped as general service e-commerce sites and specific service e-commerce sites. Thus, two homogeneous groups were formed from the large heterogeneous group. In the second part of the study, the criteria were compared and sorted using the spherical fuzzy Analytic Hierarchy Process (AHP) method.

E-Ticaret, bir web sitesindeki herhangi bir ürün veya hizmet için çeşitli ödeme yöntemleriyle alım satım yapılmasına veya sipariş verilmesine olanak sağlayan bir alışveriş yöntemidir. Bu yöntem her geçen gün önem kazanmakta ve pazar payını arttırmaktadır. Tüketicilerin e-ticareti tercih etme nedenleri birbirinden farklı olsa da genel olarak zaman, ödeme seçenekleri ve bireyselleşme gibi kriterler tercihleri etkilemektedir. Bu çalışmada; e-ticaret siteleri karşılaştırılmış ve uzman görüşleri doğrultusunda alternatif olarak 14 e-ticaret sitesi belirlenmiştir. Belirlenen bu e-ticaret siteleri marka imajı ve güvenilirliği, kampanya, kargo hızı, paketleme, ödeme seçenekleri, personel, çağrı merkezi hizmetleri ve uygulamanın işlevselliği gibi kriterler açısından değerlendirilmiştir. Çalışmanın ilk bölümünde, küme analizi kullanılarak iki e-ticaret sitesi kümesi oluşturulmuştur. Bu kümeler genel hizmet e-ticaret siteleri ve özel hizmet e-ticaret siteleri olarak gruplandırılmıştır. Böylece büyük heterojen gruptan iki homojen grup oluşturulmuştur. Çalışmanın ikinci bölümünde ise, küresel bulanık Analitik Hiyerarşi Prosesi (AHP) yöntemi kullanılarak kriterler karşılaştırılmış ve sıralanmıştır.
Kümeleme ve küresel bulanık analitik hiyerarşi süreci ile e-ticaret işletmeleri için strateji geliştirme üzerine bir çalışma
Keywords: E-Commerce; Clustering; Analytical Hierarchy Process; Fuzzy Logic; E-Ticaret; Kümeleme; Analitik Hiyerarşi Süreci; Bulanık Mantık